2019
DOI: 10.1039/c9py00190e
|View full text |Cite
|
Sign up to set email alerts
|

Selective or living organopolymerization of a six-five bicyclic lactone to produce fully recyclable polyesters

Abstract: A ring-fused γ-butyrolactone can be selectively ring-open polymerized at room temperature by N-heterocyclic carbenes to cyclic polyester or by bifunctional (thio)urea and base pairs in a living fashion to high molecular weight linear polyester that can be organocatalytically and quantitatively recycled at 120 °C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 43 publications
0
34
0
1
Order By: Relevance
“…The same group recently presented the organocatalytic ROP of similar six-five bicyclic lactone (4, to produce high molecular weight recyclable polyesters utilizing organobase/ (thio)urea binary catalysts. 19 Despite the success achieved in recyclable polymers over the past several years, fully recyclable polymeric materials are still limited, especially those with functional groups. Lu et al 20 recently developed recyclable polythioesters from biomass-sourced bridged bicyclic thiolactones with side chain allyl functional groups, which can be further modified and provide opportunities to adjust the polythioesters' properties.…”
Section: Introductionmentioning
confidence: 99%
“…The same group recently presented the organocatalytic ROP of similar six-five bicyclic lactone (4, to produce high molecular weight recyclable polyesters utilizing organobase/ (thio)urea binary catalysts. 19 Despite the success achieved in recyclable polymers over the past several years, fully recyclable polymeric materials are still limited, especially those with functional groups. Lu et al 20 recently developed recyclable polythioesters from biomass-sourced bridged bicyclic thiolactones with side chain allyl functional groups, which can be further modified and provide opportunities to adjust the polythioesters' properties.…”
Section: Introductionmentioning
confidence: 99%
“…[61][62][63][64][65][66][67] Such a method has been applied to the ROP of lactones, and LA to prepare cyclic polyesters. [68][69][70] Recently, Yang's group 71 demonstrated that a Lewis-pair catalytic system, a primary amine (1-hexyl-NH 2 ) as a Lewis base and Zn(C 6 F 5 ) 2 as a Lewis acid (Scheme 3b), could mediate the controlled ROP of OCAs. Note that such a Lewis pair has been applied for ROPs of LA and ε-caprolactone.…”
Section: Metal Catalysts For O-carboxyanhydride Polymerizationmentioning
confidence: 99%
“…Only oligomers were produced with a maximum value of 20% of monomer conversion [72,73]. The polymerization of αOHγBL was carried out at 90 °C using TfOH, producing oligomers with dehydration [56].…”
Section: Brønsted Acid-catalyzed Rop/rocp Of γ-Lactonesmentioning
confidence: 99%
“…Fluorosulfonic acid (FSO3H), TfOMe and TfOH were quite helpful to copolymerize γBL (or (R)-γVL) with different comonomers such as glycolide, 3,4-trans cyclohexylring-fused γBL (3,4-T6L) or βBL, allowing up to 30% of γBL incorporation into low molar mass copolyester chains [62][63][64][65]73]. Phosphoric acid (H3PO4) could also achieve the copolymerization of γBL, γVL or γCL with εCL in bulk at 200 °C [74].…”
Section: Brønsted Acid-catalyzed Rop/rocp Of γ-Lactonesmentioning
confidence: 99%
See 1 more Smart Citation